2004
DOI: 10.1308/147870804344
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in acute plastic surgical trauma and burns

Abstract: T elemedicine is a relatively new development within the UK, but is increasingly useful in many areas of medicine including plastic surgery.1,2 It is widely felt that telemedicine has the potential to improve patient care within health care systems through cost saving and time efficiency in patient care.3 It is already being used with great success in many hospitals in the US and Australia as well as the military service within the UK. DefinitionTelemedicine is the assessment and review of patient information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 6 publications
0
41
0
2
Order By: Relevance
“…28 Rural GPs were especially able to benefit patients (relating to timely management and avoiding unnecessary travel over distance) by using email to share digital images with urban secondary care colleagues; this has also been of value in diverse parts of the world. [29][30][31][32][33][34] Differing approaches to the integration and sharing of patient-specific email communication were in evidence, as reported elsewhere. 6 Waldren and colleagues called for such communication to be 'seamlessly interfaced' with EHR software systems to maintain the integrity of the record, avoid potential for transcription errors, and to increase quality of care and patient safety.…”
mentioning
confidence: 54%
“…28 Rural GPs were especially able to benefit patients (relating to timely management and avoiding unnecessary travel over distance) by using email to share digital images with urban secondary care colleagues; this has also been of value in diverse parts of the world. [29][30][31][32][33][34] Differing approaches to the integration and sharing of patient-specific email communication were in evidence, as reported elsewhere. 6 Waldren and colleagues called for such communication to be 'seamlessly interfaced' with EHR software systems to maintain the integrity of the record, avoid potential for transcription errors, and to increase quality of care and patient safety.…”
mentioning
confidence: 54%
“…1,3 Telemedicine has been suggested as a tool for facilitating trauma management but has yet to gain widespread popularity. 8 Wound infection rates of up to 7% have been found on review of traumatic injuries. 9 Rates of antibiotic prophylaxis varied for each scenario in this survey: 30% would consider prescribing antibiotics for a dirty wound, 13% for a complex lip wound and only 2% for an extensive forehead wound.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical priority was organised into five groups of immediate, urgent (<6 hours), very soon (<24 hours), soon (<48 hours) and later (>48 hours). The correlation coefficient was 0.78 to 0.81 for grading of the injury and 0.87 to 0.93 for priority of injury (Jones et al 2004). …”
Section: Fig 1 Qvh Trauma Card To Collect Data On All Referralsmentioning
confidence: 95%
“…Poor image quality can affect a clinician's ability to make a clear diagnosis (Briggs et al 1998;Stutchfield et al 2007); if necessary additional images should always be requested. Our own pilot study (pilot study 1) demonstrated 800 x 600 pixel resolution was adequate for diagnosis and grading of urgency of transfer (Jones et al 2004). This concurs with other telemedicine studies of wound assessment (Wirthlin et al 1998;Murphy et al 2006) and dermatology (Eedy & Wootton 2001;Krupinski et al 2008).…”
Section: 21a Image Resolutionmentioning
confidence: 95%